Diagnostics of Customer Satisfaction in the Hospitality Industry: Evidence from Nigeria - Chinedum, Nduka; Rejoice Ebere; Chris-Nnamchi, Okocha; Nwakaego, Joy (British Journal of Marketing Studies, 2017)
Nigeria in the last few decades has experienced a tremendous growth in the number of public and private hotels. The biggest challenge in today’s competitive business environment is how to retain customers and ensure customer loyalty. Also, Guest relationships in the hotel industry are strategic assets of the organization and customer satisfaction becomes the starting points to defining business objectives. The study therefore analyzed the indices of customer satisfaction in the hospitality industry in Nigeria. The research analyzed the significance of key factors that determine customer satisfaction. A structured questionnaire on staff performance, cost, hotel facilities, environment and porn accessibility was developed and used to collect information from the study sample. The structured questionnaire was administered to 400 respondents purposively. Descriptive statistics and regression analysis were used to analyze the data. The result showed that cost, hotel environment, hotel facilities and income respectively were seen to have a strong impact on customer satisfaction at 5% level of significance, while staff performance seems significant at 10%. There was a relationship between service quality and customer satisfaction. The study makes a significant contribution to the service quality management literature because few empirical studies are available dealing with this aspect of the hotel management in Nigeria. It would also help service providers in the hotel industry to understand aspects of service variables that need urgent improvement.